Green synthesis of new pyrrolidine-fused spirooxindoles via three-component domino reaction in EtOH/H2O. Issue 11 (2nd February 2018) - Wang, Yong-Chao; Wang, Jun-Liang; Burgess, Kevin S.; Zhang, Jiang-Wei; Zheng, Qiu-Mei; Pu, Ya-Dan; Yan, Li-Jun; Chen, Xue-Bing
Abstract : An efficient, green and sustainable approach was developed for the synthesis of novel polycyclic pyrrolidine-fused spirooxindole compounds. Abstract : An efficient, green and sustainable approach for the synthesis of novel polycyclic pyrrolidine-fused spirooxindole compounds was developed. The synthesis included a one-pot, three-component, domino reaction of ( E )-3-(2-nitrovinyl)-indoles, isatins and chiral polycyclic α-amino acids under catalyst-free conditions at room temperature in EtOH–H2 O. The salient features of this methodology are eco-friendliness, high yields and the ease of obtaining target compounds without the involvement of toxic solvents and column chromatography. These novel polycyclic pyrrolidine-fused spirooxindoles provide a collection of structurally diverse compounds that show promise for future bioassays and medical treatments.